Batas aman konsumsi ikan tongkol Pasar Dupa Pekanbaru ditinjau dari kandungan logam Pb dan Cu - Fitria Roza; Efriyeldi Efriyeldi; Rasoel Hamidy (Jurnal Zona, 2018)
Based on toxicology viewpoint, heavy metals can be divided into 2 types. The first type is essential heavy metals, which is in a certain amount is needed by living organisms, but in excessive amounts can cause toxic effects, such as Zn, Cu, Fe, Co and Mn. The second type is non-essential, which is in the organism body is still not known the benefit of this heavy metals even it can be become a toxic in our body, such as Hg, Cd, Pb and Cr.The purpose of this research is to 1) analyzing the concentration of heavy metals Pb and Cu  on the tuna fish which is sold in the Dupa Market Pekanbaru, and 2)analyzing the content of heavy metals Pb and Cu on Tuna,whether it has exceeded or not the threshold of SNI 2009. The study has been conducted in June to July 2015 in Dupa Market Pekanbaru City. The method used in this study is a survey method. The result showed that heavy metals Pb and  Cu have the highest metal content are derived from Sibolga waters. The heavy metals content of  tuna in  Dupa Market of Pekanbaru were Pb of 1 – 3.98 ug/g and Cu of 0.22  - 0.93 ug/g,. The Safety limit consumption of tuna in Dupa Market Pekanbaru are Pb of 3.89 kg/week and Cu of 2456.76 kg/week. Based on this results showed the status for heavy metals of Pb and Cu on Tuna fish that sold at Dupa Market Pekanbaru is still safe and consumable.